Chest wall TB and low 25-hidroxy-vitamin D levels in a 15-month-old girl - Buonsenso Danilo; Focarelli Benedetta; Scalzone Maria; Chiaretti Antonio; Gioè Claudia; Ceccarelli Manuela; Valentini Piero (BMC, 2012)
Abstract Parietal chest wall tuberculosis is an extremely rare manifestation of tuberculosis (TB) in children. We present the case of a 15 month-old girl presenting with a chest wall lesion initially thought to be of neoplastic origin and eventually diagnosed as chest wall TB, which was treated with surgical debridement and specific antitubercular therapy. The girl had not-measurable 25-hidroxy-vitamin D levels, an increasingly recognized risk factor for the development of active TB. To our knowledge, in the English literature there are no similar described cases in such young infants. This case highlight the possibility of dealing with TB and its different manifestations also in low TB burden countries, due to continuously increasing migration flows. A detailed history is a key point to reach the diagnosis. Moreover, our case confirm the possible non casual relationship between TB and low 25-hidroxy-vitamin D levels, pointing out the importance of measuring its levels in all TB patients and considering its supplementation in addition to specific antitubercular therapy.